Impacts of urbanization on land use, air quality, and temperature dynamics in Dehradun district of Uttarakhand, India: a comprehensive analysis - Dhankar, Sneha; Singh, Gayatri; Kumar, Krishan (Frontiers in Environmental Science, 2024)
The present study investigates the impact of urbanization on land surface temperature and air quality in Dehradun district of the Uttarakhand state in India. We utilized data from LANDSAT, TROPOMI, OMI, MODIS, MOPITT, and CHIRPS, for spatio-temporal and trend analyses along with the assessment of correlation matrix. Our findings revealed a significant increase in the built-up area of Dehradun district in 2023 as compared to 2003. This expansion was particularly prominent in the southern and south-eastern regions of the district. The findings highlight the impact of rapid urban expansion on land use and land cover, leading to a rise in land surface temperature (LST) and the formation of surface urban heat islands (SUHI). Notably, the study reveals distinct spatial and temporal patterns, with lower regions of Dehradun district experiencing higher temperatures and pollutant concentrations due to intensified urbanization. Dehradun city also emerged as a hotspot for nitrogen dioxide within the district. Long-term trends indicate a rise in formaldehyde and nitrogen dioxide, attributed to both urbanization and increasing temperatures, while carbon monoxide levels decrease due to reduced biomass burning and the adoption of cleaner household fuels. Correlation matrix analysis underscores the complex relationships between land use, temperature, and pollutants, with built-up areas exhibiting strong positive correlations with all pollutants. This comprehensive study highlights the importance of sustainable urban planning and management to mitigate the adverse effects of rapid urbanization on air quality and overall environmental health in the Dehradun district.